Study protocol: a core outcome set for perinatal interventions for congenital diaphragmatic hernia - Simen Vergote; Felix De Bie; Jan Bosteels; Holly Hedrick; James Duffy; Beverley Power; Alexandra Benachi; Paolo De Coppi; Caraciolo Fernandes; Kevin Lally; Irwin Reiss; Jan Deprest (Trials, 2021)
Abstract Background Congenital diaphragmatic hernia (CDH) is, depending of the severity, a birth defect associated with significant mortality and morbidity. Prenatal screening by ultrasound may detect this condition and comprehensive assessment of severity is possible, allowing for in utero referral to an experienced centre for planned delivery. In an effort to improve outcomes, prenatal interventions to stimulate lung development were proposed. Along the same lines, new postnatal management strategies are being developed. In order to enable proper comparison of novel perinatal interventions as well as outcomes, a set of uniform and relevant outcome measures is required. Core outcome sets (COS) are agreed, clearly defined sets of outcomes to be measured in a standardised manner and reported consistently. Herein we aim to describe the methodology we will use to define a COS for perinatal and neonatal outcomes of foetuses and newborns with congenital diaphragmatic hernia and to draft a dissemination and implementation plan. Methods We will use the methodology described in the Core Outcome Measures in Effectiveness Trials (COMET) Initiative Handbook. An international steering group will be created to guide the development of the COS. We are systematically reviewing the literature to identify all potential relevant pre- and neonatal outcomes previously used in studies on perinatal interventions for CDH. We will build a consensus on these core outcomes in a stakeholder group using the Delphi method. After completion, a stakeholder meeting will decide on a final COS, using a modified Nominal Group Technique. Thereafter, we will review potential definitions and measurements of these outcomes, and again a consensus meeting will be organised, to finalise the COS before dissemination. Discussion We have started a procedure to develop a COS for studies on perinatal interventions for congenital diaphragmatic hernia, with the purpose of improving the quality of research, guide clinical practice and improve patient care and eventual use in future clinical trials, systematic reviews and clinical practice guidelines. Trial registration We prospectively registered this study in the International Prospective Register of Systematic Reviews (PROSPERO) (registration number: CRD42019124399 ) and The Core Outcome Measures in Effectiveness Trials (COMET) Initiative (registration number: 1296 ).